1996
DOI: 10.2337/diacare.19.5.441
|View full text |Cite
|
Sign up to set email alerts
|

Increased Tissue Factor Pathway Inhibitor Activity in IDDM Patients With Nephropathy

Abstract: Inhibition of factor Xa activity is increased in IDDM patients with nephropathy, mainly because of increased plasma TFPI activity. The increased plasma TFPI activity in these patients may be associated with and regulated by LDL in plasma and metabolic control. The anticoagulant activity of TFPI may attenuate the hypercoagulable state in diabetes but does not seem to be able to normalize hemostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 30 publications
2
26
0
2
Order By: Relevance
“…Yokoyama et al [22] observed that TFPI concentrations were increased in insulin-dependent diabetes mellitus patients compared with control individuals. They also observed that increased plasma TFPI activity in these patients may be associated with and regulated by lowdensity lipoprotein in plasma and metabolic control individuals.…”
Section: Discussionmentioning
confidence: 98%
“…Yokoyama et al [22] observed that TFPI concentrations were increased in insulin-dependent diabetes mellitus patients compared with control individuals. They also observed that increased plasma TFPI activity in these patients may be associated with and regulated by lowdensity lipoprotein in plasma and metabolic control individuals.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, several reports claim that diabetes mellitus is associated with changes in the hemostatic system [6,7,8]. Such changes are more pronounced in patients with diabetic nephropathy than in diabetic patients without renal complications [9,10,11,12,13,14,] again suggesting that coagulation activation is associated with diabetic nephropathy.…”
Section: Introductionmentioning
confidence: 94%
“…The presence of fibrin, the final product of the coagulation cascade, in glomeruli suggests a role for the blood coagulation system in the pathogenesis of diabetic nephropathy [4, 5]. To some extent this process may be influenced by the hypercoagulable state of blood from diabetic patients, which is even more pronounced in patients with nephropathy [9,10,11,12,13,14]. In analogy with other renal diseases, we speculated that local activation of the blood coagulation system, particularly the production of TF and specific proteases such as thrombin that may induce biological effects unrelated to fibrin formation, would contribute to organ damage.…”
Section: Discussionmentioning
confidence: 99%
“…Growth factors such as transforming growth factor-b (TGF-b), which could be extraordinarily enhanced by hyperglycemia, elevated levels of systemic blood pressure and intraglomerular pressure, and glycated proteins in patients with diabetes, would affect synthesis of extracellular matrix proteins within glomerular basement membrane and vascular wall [41]. Moreover, a number of proteins (i.e., lipoprotein lipase, tissue factor pathway inhibitor, platelet factor 4, and antithrombin III) are anchored to the vascular wall via interaction with the chains of HS-PG [11,42,43]. Such alterations may potentiate albuminuria and several of the processes involved in atherogenesis [41].…”
Section: Disease Processmentioning
confidence: 99%